Trauma-related wound infections among patients admitted to emergency teaching hospital in Duhok province, Iraq - Alnakshabandie, Wasan Madhat Yousif; Mammani, Ismaeil Mohammed Abdulkahar (The Journal of Infection in Developing Countries, 2023)
Introduction: Wound infection is one of the universal challenges for patients who visit the hospital after trauma and undergo surgery and/or during their admission. Trauma could be due to Road Traffic Accidents (RTA), violence, or Falling from High (FFH). There is tangible evidence of the scope and the danger of hospital-acquired infections, which are far more common and deadly than many people comprehend. Methodology: 280 samples were collected from 140 injured persons, who attended the Emergency Teaching Hospital in Duhok, Iraq from September 2021 to April 2022. 140 samples were collected on the patients’ arrival and 140 samples after admission and treatment. The isolated bacteria were manually diagnosed, and then VITEK®2 compact system was performed for confirmation. Results: 27 microbial species were identified. The common bacterial species detected on patients’ arrival were Staphylococcus epidermidis 22 (19.6%), Escherichia coli 16 (14.3%), Staphylococcus aureus 14 (12.5%), Staphylococcus lentus 10 (8.9%) and Stenotrophomonas maltophilia 6(5.4%). On the 2nd samples, which were collected after patients’ admission, the species were Staphylococcus aureus 35(31.3%), Escherichia coli 13(11.6%), Pseudomonas aeruginosa 12 (10.7%), Staphylococcus epidermidis 10 (8.9%), Acinetobacter baumannii and Klebsiella pneumonia were 8 (7.1%) each. Conclusions: The bacteria that contaminate wounds at the accident time led to serious problems after the admission as they cause wound infection with inappropriate antibiotic administration. It is established that there are differences between the bacterial species detected before and after admission in this study with p = 0.004. Furthermore, it has been demonstrated that some species that are isolated prior to the admission of patients turn hostile afterward.